2013
DOI: 10.1534/genetics.113.149849
|View full text |Cite
|
Sign up to set email alerts
|

Novel Connections Between DNA Replication, Telomere Homeostasis, and the DNA Damage Response Revealed by a Genome-Wide Screen for TEL1/ATM Interactions in Saccharomyces cerevisiae

Abstract: Tel1 is the budding yeast ortholog of the mammalian tumor suppressor and DNA damage response (DDR) kinase ATM. However, tel1-D cells, unlike ATM-deficient cells, do not exhibit sensitivity to DNA-damaging agents, but do display shortened (but stably maintained) telomere lengths. Neither the extent to which Tel1p functions in the DDR nor the mechanism by which Tel1 contributes to telomere metabolism is well understood. To address the first question, we present the results from a comprehensive genome-wide screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…We, and others, have uncovered genetic interactions with tel1 Δ in response to DNA-damaging agents. Two previous studies demonstrated that tel1 Δ in combination with mutations affecting 9-1-1 DDR checkpoint genes are more sensitive to CPT, ionizing radiation, and the alkylating agent MMS ( Guenole et al 2013 ; Piening et al 2013 ). Piening and co-workers also identified 10 interactions with tel1 Δ that were specific to treatment with MMS.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have uncovered genetic interactions with tel1 Δ in response to DNA-damaging agents. Two previous studies demonstrated that tel1 Δ in combination with mutations affecting 9-1-1 DDR checkpoint genes are more sensitive to CPT, ionizing radiation, and the alkylating agent MMS ( Guenole et al 2013 ; Piening et al 2013 ). Piening and co-workers also identified 10 interactions with tel1 Δ that were specific to treatment with MMS.…”
Section: Discussionmentioning
confidence: 99%
“…These included Yku70, members of the 9-1-1 pathway, the CCR4-NOT deadenylase complex, nuclear pore components, and several histone deacetylases. Most of these mutants caused the MMS sensitivity due to their effects on telomeres (Piening et al, 2013).…”
Section: Systems Biology Of Telomere Biologymentioning
confidence: 99%
“…The mec1 mutant is considered to be much more sensitive to DNA-damaging agents than the tel1 mutant (Greenwell et al 1995 ; Morrow et al 1995 ). However, under certain conditions (e.g., depletion of dNTP pools through pretreatment with HU), the tel1 cells were found to be methyl methanesulfonate (MMS)-sensitive compared to wild-type cells (Piening et al 2013 ). More recently, it has been reported that Tel1p has two functions in checkpoint response to DSBs (Mantiero et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%